Correction: Park et al. Effect of Particulate Matter 2.5 on Fetal Growth in Male and Preterm Infants through Oxidative Stress. Antioxidants 2023, 12, 1916 - Sunwha Park; Eunjin Kwon; Gain Lee; Young-Ah You; Soo Min Kim; Young Min Hur; Sooyoung Jung; Yongho Jee; Mi Hye Park; Sung Hun Na; Young-Han Kim; Geum Joon Cho; et al. (MDPI AG, 2024)
In the original publication [...]